CLASSIFICATION OF THREATS TO STATE INFORMATIVE RESOURCES OF NORMATIVELY-LEGAL ASPIRATION. METHODOLOGY OF CONSTRUCTION OF CLASSIFIER - Юдін, Олександр Костянтинович; Бучик, Сергій Степанович (Ukrainian Information Security Research Journal, 2015)
In the article the analysis of their last researches and publicationson the subjects of construction of methodologyof classifier of threats of state informative resources generalizedby the authors is conducted. It is indicated thatthe method of «double three of security» offered by authorsis the fundamental for forming of «Classifier ofthreats of state informative resources» which is formed onthe basis of the two platforms of security. The first platformof informative safety consists of elements which aresubject to security (properties of information): confidentiality;integrity; availability. The second platform of informativesafety consists of components which realize thesystem of security (methods and facilities): normativelylegal;organizational; technical. The place of threats ofstate informative resources of normatively-legal aspirationin the general system of classifier is shown. Clarificationof semantics of classifier taking into account division ofthreats into strategic and tactical is carried out. Strategicthreats concern the questions of national security, absenceor non-fulfillment of the special purpose programs ordoctrines, weakening of branch intercommunications oforgans of state and legislative power and others like that.Tactical threats directed to the informative systems oftreatment, storage and transmission of state informativeresources. Certain threats of normatively-legal aspirationwith taken into account experience of the authors, existentnormatively-legal base and other information sourcesare defined. For the realization of further codificationevery threat is attributed to the certain parameters: accordingthe source of threat; in relation to informationholding object; by the nature of threats; by the structureof influence; by the level of influence. The ways of furtherresearches which must be aimed at determination ofthreats of organizational and technical character are set.Directions of further researches are set, the necessity offurther perfection of normative base with the purpose ofsecurity of state informative resources is indicated on.